Employee Motivation As A Driver Of Business Organization - Atik Maliyya; Lailatus Subhiyah; Ahmad Gianto; Taufik; Nunuk Indarti (International Journal of Technology and Education Research, 2026)
Employee motivation is a strategic factor that determines the success of a business organization in achieving operational and long-term goals. This research or discussion outlines the role of motivation as the main driver of employee productivity, performance, and commitment. Through the implementation of the right motivational strategies, both intrinsic such as self-development and recognition, and extrinsic such as compensation and a supportive work environment, organizations can create working conditions that promote increased effectiveness and efficiency. The analysis shows that motivation not only serves as a driver of work behavior, but also as an important foundation in building an adaptive, innovative, and results-oriented organizational culture. Thus, employee motivation is a key element in ensuring the sustainability and competitiveness of business organizations in the midst of changing environmental dynamics.